Hitung Nilai MPN (Most Probable Number) Coliform Pada Es Kristal Yang Diperjual Belikan Di Wilayah Kota Makassar - Devy Anggreani; Nardin Nardin; Suharsih Thahir (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
Crystalline water ice is freezing at a temperature of 00C or more and can be left back at room temperature. Ice crystals can be used as a supplement for beverages, also can be used as a means to preserve. The Ice Crystals are used as a supplementary material and can be mixed with food or beverages, then the ice crystals must be used to meet the requirements of chemistry, physics and biology. This bacteriological quality of ice is sold in Makassar area. The type of research conducted laboratory observations. After examination of the 3 samples of ice crystals, the results showed the smallest total value of MPN cells / 100 93 ml, and the largest> 2400 cells / 100 ml. The results of microbiological tests according to PERMENKES number 907 of 2002. Based on these results, the public should be more careful in buying ice crystals, more attention to personal hygiene, equipment and shelters ice crystals. Environmental conditions that are less clean place to do business with the dust, fumes and others can be made of contamination and the local health department. marketed.